Fresno County Counsel Baby Shower for Leticia Aleman - Watkins, Howard::::::::: (1987)
Debbie Lucas, Phillip Jay, Leticia Aleman, John Duffy, Vickie Stoutingberg and James Waterman holding coffee cup and